The study of 11th Sarawak State Election: candidate personality versus party identification case study Kota Samarahan / Glenn Eric Ringib and Justine Ulok Gana - Ringib, Glenn Eric; Gana, Justine Ulok (2014)
This paper examines on the coming 11th Sarawak State Election especially on the voter’s preferences whether they vote based on candidate personality or political party identification in P. 197, Kota Samarahan for it’s as the targeted population for this study. This paper will focus on these two factors; candidate personality and political party identification that could influence the voter preferences. Under many electoral systems voters can choose between candidates and under some, between candidates of the same party or other parties, a situation that makes it possible for voters to choose the best factors which is influence them to vote. This paper uses an extensive set of instruments to study and explore the extent to which voters decide on candidate personality factors as opposed to political party identification ones. Historically, the electoral behavior in Sarawak tends to focused on political party choice because the political competition is closely relative to its demographic structure where the state Barisan Nasional party has enjoyed preeminence at the polls in all election. When it comes to the current political situation, there is recognition that the political party identification is not all matters and that personal attributes of the candidates have an importance roles in campaign of election. Yet there is a significant and growing literature that argues that candidate personality should be and are important sources of votes in many elections.